Telepractice in providing speech therapy for children: Speech therapists’ view and experiences - Kairiene, Daiva; Gajauskienė, Aušra (Special Education, 2022)
The article analyses speech therapists’ view and experiences in providing speech therapy using telepractice in the context of the COVID-19 situation. The performed quantitative and qualitative analysis of the research data revealed how the country’s speech therapists perceived telepractice, the types of applied telepractice, the advantages and limitations of applying this practice, the opportunities to provide (in)direct support to children who had various speech, language and swallowing disorders, and the opportunities to perform professional quality functions from a distance. The study revealed that telepractice in the speech therapist’s work, although challenging due to the need to apply it in unforeseen circumstances and without proper preparation, had many advantages and could be successfully applied when combined with normal, traditional, in-person support.